Asian family business case studies : the role of culture, value and identity in succession and resilience - Feranita, Feranita; Lin, Woon Leong; Khong, Kok Wei; Goh, See Kwong (Emerald Publishing Limited, 2024)
Family business is the backbone of the global economy, as they account for seventy to ninety percent of all businesses worldwide. Although research on family business started in 1960's, much of the extant literature is still based on data from the West. Examining beyond this limited context is especially important, as Asia has a vast variety of ethnicities, cultures and values influencing how families in business behave. In Asian Family Business Case Studies, specialists from around the globe offer detailed case studies covering a variety of topics including succession planning, conflict resolution, overcoming COVID 19, values and identity, CSR, green innovation, sustainability, internationalization, transformation, family relation, communications, and entrepreneurship. With insider case stories gathered firsthand from real family businesses owned and managed by Asian families around the world, this collection provides in-depth insights to academicians, students, family business managers/owners/successors, and practitioners. Each chapter is a standalone case study on a family business with a specific theme. At the end of each chapter, questions are provided to prompt discussions for learning purposes.